Individual electric field in cortical white matter is correlated with cognitive improvement in patients with mild cognitive impairment due to Alzheimer's disease after repetitive transcranial magnetic stimulation treatment - Liang, Junhua; Wang, Qianqian; Wang, Jiahao; Shao, Yuxuan; Zhu, Shuxiang; Wu, Nianshuang; Huo, Xiaolin; Zhang, Guanghao; Lin, Hua (Journal of Alzheimer's disease, 2025)
BackgroundRepetitive transcranial magnetic stimulation (rTMS) may be effective for Alzheimer's disease (AD) and mild cognitive impairment (MCI); however, the therapeutic efficacy varies significantly, highlighting the need for reliable biomarkers to predict treatment response. While rTMS may activates cortical white matter, the relationship between induced electric field (E-field) in this region and clinical outcomes remains unclear.ObjectiveThis study characterized the E-field in cortical gray matter (EF ), cortical white matter (EF ), and region-of-interest (EF ) in the left dorsolateral prefrontal cortex (DLPFC), and explored their correlations with treatment efficacy in patients with MCI due to AD.MethodsThirty patients with MCI due to AD received 2-week rTMS treatment, with efficacy measured by Auditory Verbal Learning Test (AVLT) and a comprehensive neuropsychological battery. Responders were defined as those with >25% improvement in AVLT-immediate memory. Correlations between regional brain volumes and E-field magnitudes, and the correlations between E-field magnitudes and cognitive improvement, were analyzed. Predictive performance of E-fields for responder classification was evaluated.ResultsPronounced inter-individual variability in magnitudes of EF EF and EF was observed, partially explained by differences in regional brain volumes of DLPFC targeted area. Treatment responders exhibited significantly higher EF magnitude. EF positively correlated with AVLT-immediate memory improvement (R = 0.37) and predicted responder groups, achieving an area under the curve (AUC) of 0.76.ConclusionsE-field within cortical white matter in the DLPFC correlates with rTMS efficacy and predicts therapeutic response in MCI due to AD. Personalized stimulation protocols incorporating EF modeling may optimize treatment parameters.Trial registrationThis study is registered in the Chinese Clinical Trial Registry, number ChiCTR2200062564, date of registration: 2022-08-11.